THE FACTORS THAT INFLUENCING EMPLOYEE’S WORK PERFORMANCE IN PT. TALISMAN INSURANCE BROKERS - Dini Rahmawati; Parlagutan Silitonga (Human Capital Development, 2016)
Purpose- . Aiming to findout the The Factors That Influencing Employee’s Work Performance In PT. Talisman Insurance Brokers. Design/methology/approach- A questionaire as instrument of survey to respondent of employees in In PT. Talisman Insurance Brokers. The sample were 91 respondents derived by Slovin formula, within a single organization supported by interviews. Findings- Based on F-test,it is concluded that Organizational communication and Compensation simultaneously have effected the work motivation of the employee in In PT. Talisman Insurance Brokers. It it double checked, the result of t-test is also confirming that Organizational communication and Compensation simultaneously have effeFinally the coorelation and determinant test is applied that this is also determines that there is a real relationship among the two varibales against the work motivation of the employees In PT. Talisman Insurance Brokers. Research limitations-However the capacity of independent variables to influence the effect on work motivation is weaker than other variables, that are not included in this research. Practical implications-The manager of human resource shall maintain the authentic information by means of available organizational communications. Additionally that this is a main area to evaluate the existing compensation as it has bigger effect on work motivation. The Originality-This is done exclusively for the single company that may applicable therein